TRANSFORMASI PEMBELAJARAN AKUNTANSI : EFEKTIVITAS KOMIK DIGITAL BERBASIS PROBLEM-BASED LEARNING(DI SMK WILAYAH KECAMATAN SETIABUDI, JAKARTA SELATAN) - Holiawati Holiawati; Iryanis Iryanis; Dian Widiyati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The purpose of this study is to examine differences between classes in the transformation of accounting learning by comparing a control class and an experimental class regarding the effectiveness of Problem-Based Learning based Digital Accounting Comics in vocational high schools in the Setiabudi District, South Jakarta. The study is motivated by the need for accounting instruction that is more engaging, contextual, and capable of improving students’ understanding through the integration of digital learning media and problem-based learning.This research employs a quantitative comparative approach using a quasi- experimental design, comparing learning outcomes between a group receiving the treatment and a group taught using conventional instruction. Research data were collected through learning outcome tests administered before and after the intervention, as well as a questionnaire to capture students’ responses to the use of Digital Accounting Comics in the learning process. The research subjects constitute a case study across several vocational high schools in the Setiabudi District, with implementation that differentiates the experimental class using Problem-Based Learning based Digital Accounting Comics and the control class using conventional learning.Data analysis was conducted through prerequisite tests and a difference test to assess learning outcome differences between the control and experimental classes, along with descriptive analysis to interpret trends in student responses based on the questionnaire. The results show that the experimental classes using Problem- Based Learning based Digital Accounting Comics achieved better learning outcomes than the control classes in all schools examined, and the differences met the significance criteria applied in this study. These findings confirm that Problem- Based Learning based Digital Accounting Comics are effective as an alternative instructional innovation and can support the transformation of accounting learning because they not only improve learning outcomes but also gain student acceptance through positive responses.